ASTHENOSPHERE OF THE ASIA-PACIFIC ACTIVE MARGIN AND ADJACENT PARTS OF ASIA AND THE PACIFIC - Tuyezov I.K. (My University, 1988)
In this article, by asthenosphere we mean a relatively low-viscosity layer, formed in the upper mantle because the temperature there approches the solidus temperature of rocks at those depths. If the mantle temperature exceeds the solidus temperature of such rocks, zones of partial melting will appear in this layer. At greater depths, hydrostatic pressure has a stronger effect on viscosity and melting point than the mantle temperature. This results in an increase in rock viscosity and the disappearance of zones of partial melting. All this is illustrated by the structure of the asthenosphere as established on the Lake Baikal-Pacific geotraverse.